Do Not Cut Off Aid to Israel: An increasingly fashionable view is wrong-and dangerous. - Abrams, Elliott (Commentary, 2023)
The article presents the discussion on issue of military aid from the US to Israel becoming a subject of contention, with differing opinions emerging from both the political left and right. Topics include opposing foreign aid in general, including military assistance, and seeking to reduce or eliminate it; and encompassing various forms of military assistance having provisions with direct relevance to American security interests.